2022
DOI: 10.1002/adma.202106388
|View full text |Cite
|
Sign up to set email alerts
|

An NIR Discrete Metallacycle Constructed from Perylene Bisimide and Tetraphenylethylene Fluorophores for Imaging‐Guided Cancer Radio‐Chemotherapy

Abstract: To promote the clinical theranostic performances of platinum‐based anticancer drugs, imaging capability is urgently desired, and their chemotherapeutic efficacy needs to be upgraded. Herein, a theranostic metallacycle (M) is developed for imaging‐guided cancer radio‐chemotherapy using perylene bisimide fluorophore (PPy) and tetraphenylethylene‐based di‐Pt(II) organometallic precursor (TPE‐Pt) as building blocks. The formation of this discrete supramolecular coordination complex facilitates the encapsulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 113 publications
(20 reference statements)
0
61
0
Order By: Relevance
“…These include, inter alia, avoidance of recognition through the lack of expression of MHC class I (major histocompatibility complex) molecules, loss of antigenic epitopes, inactivation of immunological cells through the production of immunosuppressive factors, expression of anti-apoptotic proteins on cancer cells and a reduction in pro-apoptotic protein expression. A number of these mechanisms are conducive to progression, creation of their own environment for the development and closure of cells in their own favorable environment [ 3 , 4 , 5 ]. Therefore, understanding what happens within the tumor microenvironment and which mechanisms are responsible for tumor development and progression will let us know how cancer could protect itself against the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…These include, inter alia, avoidance of recognition through the lack of expression of MHC class I (major histocompatibility complex) molecules, loss of antigenic epitopes, inactivation of immunological cells through the production of immunosuppressive factors, expression of anti-apoptotic proteins on cancer cells and a reduction in pro-apoptotic protein expression. A number of these mechanisms are conducive to progression, creation of their own environment for the development and closure of cells in their own favorable environment [ 3 , 4 , 5 ]. Therefore, understanding what happens within the tumor microenvironment and which mechanisms are responsible for tumor development and progression will let us know how cancer could protect itself against the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…An example of a nanotheranostic concept is the use of tetraphenylethylene-based di-Pt(II) organometallic precursor (TPE-Pt), which is a chemotherapeutic with additional properties of a radiosensitizer, sensitizing cancer cells to radiotherapy. In vitro and in vivo studies in mice showed effective inhibition of tumor growth and prolonged survival of mice with cisplatin-resistant cancer [ 103 ]. In the context of CC treatment, there are promising reports using nanoparticles and small interfering RNA (siRNA), showing the ability to inhibit genes responsible for CC invasion and development [ 104 ].…”
Section: Review Resultsmentioning
confidence: 99%
“…Due to the complexity and heterogeneity of tumors, personalized treatment is a trend. A potential way to achieve it is theranostics, which combines treatment with real-time diagnosis to provide an opportunity to monitor the effectiveness of treatment and adjust the treatment window over time [ [74] , [75] , [76] ]. Due to its high depth penetration and spatial/temporal resolution, photoacoustic (PA) imaging can guide drug release, localization, and diagnosis [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%